17 years after the start of the global financial crisis (GFC), where are we now with credit and house prices in the Irish residential market? - Paul Egan; Kieran McQuinn; Conor O'Toole (The Economic and Social Research Institute (ESRI), 2024)
The credit bubble experienced by the Irish residential and financial sector immediately prior to the global financial crisis (GFC) was one of the largest experienced across contemporary western economies. The Irish property market had witnessed a significant increase in activity as the economy was transformed during the "Celtic tiger" era. However, hand in hand with the increase in housing demand came a significant degree of credit market liberalisation which resulted in a substantial increase in the availability of mortgage credit. This in turn additionally fuelled the emerging house price bubble emerging by 2005 resulting in the Irish financial sector being especially vulnerable to the global financial crisis of 2007/08 due to its substantial liabilities in the property market. A period of significant reform in credit availability followed, as evidenced by the adoption of the Central Bank of Ireland of macroprudential rules in early 2016. Now 17 years after the crisis first impacted the Irish market and given the persistent increase observed in Irish house prices since 2012, it is prudent to examine the inter-relationship between credit availability and house price movements to see how the residential and financial market are evolving? We use a recently developed model of the Irish housing and credit sector to assess the contribution of changing credit standards to recent house price developments.
Keywords: R21; E51; G12; 330; House prices; Credit; Macroprudential